Denitrification Biokinetics: Towards Optimization for Industrial Applications - Suri, Navreet; Zhang, Yuan; Gieg, Lisa M.; Ryan, M. Cathryn (Frontiers in Microbiology, 2021)
Denitrification is a microbial process that converts nitrate (NO3-) to N2 and can play an important role in industrial applications such as souring control and microbially enhanced oil recovery (MEOR). The effectiveness of using NO3- in souring control depends on the partial reduction of NO3- to nitrite (NO2-) and/or N2O while in MEOR complete reduction of NO3- to N2 is desired. Thauera has been reported as a dominant taxon in such applications, but the impact of NO3- and NO2- concentrations, and pH on the kinetics of denitrification by this bacterium is not known. With the goal of better understanding the effects of such parameters on applications such as souring and MEOR, three strains of Thauera (K172, NS1 and TK001) were used to study denitrification kinetics when using acetate as an electron donor. At low initial NO3- concentrations (~1 mmol L-1) and at pH 7.5, complete NO3- reduction by all strains was indicated by non-detectable NO3- concentrations and near-complete recovery (> 97%) of the initial NO3-N as N2 after 14 days of incubation. The relative rate of denitrification by NS1 was low, 0.071 mmol L-1 d-1, compared to that of K172 (0.431 mmol L-1 d-1) and TK001 (0.429 mmol L-1 d-1). Transient accumulation of up to 0.74 mmol L-1 NO2- was observed in cultures of NS1 only. Increased initial NO3- concentrations resulted in the accumulation of elevated concentrations of NO2- and N2O, particularly in incubations with K172 and NS1. Strain TK001 had the most extensive NO3- reduction under high initial NO3 concentrations, but still had only ~78% of the initial NO3-N recovered as N2 after 90 days of incubation. As denitrification proceeded, increased pH substantially reduced denitrification rates when values exceeded ~ 9. The rate and extent of NO3- reduction was also affected by NO2- accumulation, particularly in incubations with K172, where up to more than a 2-fold rate decrease was observed. The decrease in rate was associated with decreased transcript abundances of denitrification genes (nirS and nosZ) required to produce enzymes for reduction of NO2- and N2O.